Endourologic treatment for a fibroepithelial ureteral polyp protruding from the urethra. Issue 11 (11th November 2019) - Abdessater, Maher; Kanbar, Anthony; Khoury, Joey El; Hachem, Charbel El; Halabi, Rami; Boustany, Johnny; Khoury, Raghid El
Abstract: Fibroepithelial polyps (FP) of the ureter are rare and benign mesodermal tumors frequently mistaken for transitional cell carcinoma. We hereby report a rare case of a 19-year-old patient with two FPs, originating from the distal left ureter that were successfully treated with ureteroscopy. One of these polyps was completely protruding outside the bladder through the urethra, which makes this case unique in the literature. Ureteroscopy is currently the best method available for identification, histologic diagnosis and treatment of these polyps.